Types Complexity of Idioms Meaning in Arabic Language Learning Materials - Ahmadi Ahmadi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
One must choose a meaningful word or sentence to reveal the intended meaning and purpose. The wrong choice of words in an idiom can be fatal. Therefore, studying and understanding several types of meanings of an idiom in the language is necessary. This study aims to provide a theoretical map of the types of expressions with different meanings in Arabic. This study uses a library research method that examines sources of information related to the idiom model in Arabic. The results of this study indicate that in Bahasa Indonesia, there are approximately twelve types of utterance meanings. The twelve types of meaning will help the language speakers determine the right choice of words to express the desired meaning. Meanwhile, in Arabic, there are approximately twelve types, including Lexical Meaning, Grammatical Meaning, Contextual Meaning, Referential Meaning, Denotative Meaning, Connotative Meaning, Conceptual Meaning, Associative Meaning, Word Meaning, Term Meaning, Idiom Meaning, and finally the meaning of proverbs.